Association of Cardiac Baroreflex Sensitivity with Blood Pressure Transients: Influence of Sex and Menopausal Status - Barnes, Jill N.; Matzek, Luke J.; Charkoudian, Nisha; Joyner, Michael J.; Curry, Timothy B.; Hart, Emma C. (Frontiers in Physiology, 2012)
The magnitude of decrease in BP during a vasoactive drug bolus may be associated with the calculated baroreflex sensitivity (BRS). The purpose of the present study was to evaluate whether sympathetic and/or cardiac BRS relates to the extent of change in BP and whether this was altered by sex hormones. Fifty-one young women (27 ± 1 yrs), 14 older women (58 ± 1 yrs), and 36 young men (27 ± 1 yrs) were studied. Heart rate, BP, and MSNA were monitored. Sympathetic BRS was analyzed using the slope of the MSNA-diastolic BP (DBP) relationship and cardiac BRS was analyzed using the RRI-systolic BP (SBP) relationship. Young women and men had similar mean arterial pressures (MAP, 91±1 vs. 90±1 mmHg), cardiac BRS (19±1 vs. 21±2 ms/mmHg), and sympathetic BRS (-6±1 vs. -7±1 AU/beat/mmHg), respectively. Older women had higher MAP (104±4 mmHg, p<0.05) and lower cardiac BRS (7±1 ms/mmHg, p<0.05), but similar sympathetic BRS (-8±1 AU/beat/mmHg). There was no association between BP transients with either cardiac or sympathetic BRS in young women. In the older women, the drop in SBP, DBP, and MAP were associated with cardiac BRS (r=0.60, r=0.59, and r=0.70, respectively; p<0.05), but not sympathetic BRS. The decrease in SBP was positively related to cardiac BRS in young men (r=0.41; p<0.05). However, there was no relationship between the decrease in BP and sympathetic BRS. This indicates that older women and young men with low cardiac BRS have larger transients in BP during nitroprusside. This suggests a more prominent role for cardiac (as opposed to sympathetic) BRS in responding to acute BP changes in young men and older women. The fact that these relationships do not exist in young women suggest that the female sex hormones influence baroreflex responses.